Effects of a Saccharomyces cerevisiae fermentation product on fecal characteristics, nutrient digestibility, fecal fermentative end-products, fecal microbial populations, immune function, and diet palatability in adult dogs. (16th February 2019) - Lin, Ching-Yen; Alexander, Celeste; Steelman, Andrew J; Warzecha, Christine M; de Godoy, Maria R C; Swanson, Kelly S
Abstract: Yeast products may serve as functional ingredients due to their benefits on host health but vary greatly in source, composition, and functionality, justifying research in host species of interest. In this study, a Saccharomyces cerevisiae fermentation product (SCFP ) was investigated as a dietary supplement for adult dogs. Adult female beagles ( n = 12; mean age = 3.3 ± 0.8 yr; mean BW = 10.3 ± 0.68 kg) were fed the same diet, but supplemented with three levels of SCFP (125, 250, and 500 mg/d) or a placebo (sucrose) via gelatin capsules in a replicated 4 × 4 Latin square design. Fecal samples for nutrient digestibility, fecal characteristics and microbial populations as well as blood samples for immune indices were collected after a 21-d adaptation phase in each period. A separate palatability test was conducted to examine palatability of an SCFP-containing diet (0.2% of diet). All data, except for palatability data, were analyzed by Mixed Models procedure of SAS (version 9.4). A paired t -test was conducted to analyze data from the palatability test. Supplementation of SCFP did not affect total tract apparent macronutrient and energy digestibilities or fecal characteristics. Fecal phenol and total phenol + indole concentrations decreased linearly with SCFP dosage ( P < 0.05). Relative abundance of Bifidobacterium was greater ( P < 0.05), while Fusobacterium was lower ( P < 0.05) in SCFP-supplemented dogs. Total white blood cell counts were decreased by SCFP ( P < 0.05). The percentage of natural killer cells and antigen-presenting cells were not altered by SCFP. However, when comparing control vs. all SCFP treatments, SCFP-supplemented dogs had greater ( P < 0.05) major histocompatibility complex class II presenting B cell and monocyte populations than control dogs. IFN-γ secreting helper and cytotoxic T cells increased linearly with SCFP consumption ( P < 0.05). Immune cells derived from SCFP-supplemented dogs produced less ( P < 0.05) TNF-α than those from control dogs when cells were stimulated with agonists of toll-like receptors 2, 3, 4, and 7/8. A linear increase ( P < 0.05) in serum IgE with SCFP dosage was noted. In the palatability test, a 1.9:1 consumption ratio was observed for the SCFP-containing diet vs. control diet, demonstrating a preference ( P < 0.05) for SCFP. Results of this study suggest that SCFP supplementation may be beneficial to adult dogs by positively altering gut microbiota, enhancing immune capacity and reducing inflammation.